The need for enhancing green infrastructure strategies towards carbon–neutral city - Wan Daud, Wan Masyitah; Ibrahim, Roziya (Springer Nature, 2025)
Rapid urbanization is a double-edged sword for cities, bringing opportunities and challenges. While it promotes economic growth and creates a higher standard of living, it also strains the infrastructure, degrades the environment, and leads to increased air pollution with high levels of carbon emissions, affecting the health and well-being of urban residents. Furthermore, cities like Greater Kuala Lumpur, Malaysia are vulnerable to the impacts of climate change. To address these challenges, designing cities to be more liveable, resilient, and achieve carbon–neutral targets has become an imperative demand to meet the Sustainable Development Goals (SDGs) by 2030. A comprehensive ecological solution in green infrastructure is gaining prominence in urban landscape planning to cope with the impact of climate change. This paper aims to formulate a conceptual framework of ecological solutions for enhancing green infrastructure strategies for city carbon reduction purposes. It reviewed related literature to explore the historical background, trends, and evolutions of the ecological solutions through and justifies the need for such an approach to improve urban performance for long-term sustainability. The proposed framework will serve as a foundational reference for applying ecological solution in green infrastructure planning for carbon reduction. The findings will contribute to urban landscape planning for enhancing green infrastructure strategies and achieving carbon–neutral city targets by 2050.